Two Decades of Income Inequality in Britain: The Role of Wages, Household Earnings and Redistribution. (17th January 2017) - Belfield, Chris; Blundell, Richard; Cribb, Jonathan; Hood, Andrew; Joyce, Robert
Abstract : We study earnings and income inequality in Britain over the past two decades, including the period of relatively 'inclusive' growth from 1997 to 2004, and the Great Recession. We focus on the middle 90%, where trends have contrasted strongly with the 'new inequality' at the very top. Household earnings inequality has risen, driven by male earnings—although a 'catch‐up' of female earnings did hold down individual earnings inequality and reduce within‐household inequality. Nevertheless, net household income inequality fell due to deliberate increases in redistribution, the tax and transfer system's insurance role during the Great Recession, falling household worklessness, and rising pensioner incomes.